2022
DOI: 10.1292/jvms.21-0480
|View full text |Cite
|
Sign up to set email alerts
|

Endemic infections of bovine viral diarrhea virus genotypes 1b and 2a isolated from cattle in Japan between 2014 and 2020

Abstract: Note, Virology Endemic infections of bovine viral diarrhea virus genotypes 1b and 2a isolated from cattlein Japan between 2014 and 2020

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…[9] and Nishimori et al [15] are in accordance with that in our study and further confirms that subgenotype 1b is the most important BVDV subgenotype endemic in Tokachi Province. Commercial inactivated and live-attenuated vaccines based on BVDV subgenotypes 1a and 2a strains and commercial inactivated vaccines containing BVDV 1b and 2a are available in Japan [20].…”
supporting
confidence: 93%
See 3 more Smart Citations
“…[9] and Nishimori et al [15] are in accordance with that in our study and further confirms that subgenotype 1b is the most important BVDV subgenotype endemic in Tokachi Province. Commercial inactivated and live-attenuated vaccines based on BVDV subgenotypes 1a and 2a strains and commercial inactivated vaccines containing BVDV 1b and 2a are available in Japan [20].…”
supporting
confidence: 93%
“…However, Nishimori et al . [ 15 ] showed that the result of subgenotyping based on 5′ UTR region was consistent with that based on the E2 gene region. In contrast, another study reported the mismatch in the results of subgenotyping of 5′ UTR- and E2 gene-based analysis [ 19 ].…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…BVDV belongs to the plague virus genus of the Flaviviridae family. The viral genome is a single-stranded RNA, encoding four structural proteins (i.e., C, Erns, E1, and E2) and eight non-structural proteins (i.e., Npro, p7, NS2, NS3, NS4A, NS4B, NS5A, and NS5B) [ 29 , 30 ]. Dong Kun et al [ 31 ] applied a double antibody sandwich ELISA kit for bovine viral diarrhoea virus and bovine enterovirus antigen to 738 faecal samples collected from five regions in Jilin Province in 2019–2020, respectively, and confirmed some samples with PCR and immunofluorescence tests.…”
Section: Application Of Flow Cytometry In the Diagnosis Of Bovine Epi...mentioning
confidence: 99%